The impact of Petronas independence day TV commercials among teenagers / Nur Akma Halili - Halili, Nur Akma (2014)
Advertisement is the most important medium in our daily life whether in electronic or printed media. Advertisements through the use of electronic media such as TV ads are a particularly effective communications tools to convey more effective services to the community and more effective services to the community. The objective of this research is to examine the Petronas Independence Day TV Commercials from2001 to 2010 as Public Service Announcements (PSA) in creating awareness and self-esteem among teenagers, besides that the researcher want to analyze the impact of Petronas Independence Day TV Commercials among teenagers in creating their self.esteem This research is to provide guidance to the producer, the director of photography, TV media and also to society. A Quantitative method was employed the use of questionnaires and observation to emphasize on objective measurements and numerical analysis of the data collected. The questionnaires were analysed by using SPSS software. The findings indicated that TV Commercials give an impact on selfesteem among teenagers through three main characteristics, namely cognitive effect, affective effect and behavior effect. In other words, the message that is being conveyed an important element in an advertisement to attract the attention of the audience. The study concluded and recommended that TV Commercials need to enhance the Quality of Storytelling, the Advertisement Show Times and the Presentation style as it will be ofbetter quality, were effective and impactful in the future.